Effect Of Alcohol Consumption On Rodent Periodontal Health And Improvement By The Probiotic Lactobacillus Reuteri. - Almohareb, Sadeem. (2017)
Abstract: Background: The purpose of this study was to evaluate the effect of chronic alcohol consumption, in high and low doses, on periodontal health and to investigate the potential of the probiotic Lactobacillus reuteri (L. reuteri) to counteract the deleterious effect of alcohol on periodontal health. Materials and methods: Twenty-four adult male Sprague-Dawley rats (2 months old) were divided randomly into three groups: control group consumed liquid diet (CG; n=8); low alcohol group consumed 3.1% alcohol liquid diet (LAG; n=8); and high alcohol group consumed 6.2% alcohol liquid diet (HAG; n=8). After eight weeks of alcohol consumption, the three groups were divided randomly into six subgroups to either receive L. reuteri or not. L. reuteri (DSM17938, 2×108 CFU/day and ATCC PTA5289, 2×108 CFU/day) was added daily to the liquid diet for two weeks. The periodontal parameters: plaque index (PI), bleeding on probing (BOP), and gingival index (GI); and subgingival bacterial count were measured at baseline, after eight weeks of alcohol consumption, and after 2 weeks of L. reuteri intake. Results: BOP increased in both the LAG and HAG after 8 weeks of alcohol consumption and this increase was statistically significant in the HAG [median (IQ): 6 (6.5) to 15.63 (6.25), p=0.035]. The GI score was also significantly increased in the LAG [median (IQ): 0.12 (0.18) to 0.25 (0.15), p=0.020] and in the HAG [median (IQ): 0.12 (0.13) to 0.37 (0.25), p=0.021]. There was no difference in the amount of plaque between the different groups. After two weeks of L. reuteri intake, BOP and GI were decreased in the LAG and HAG and the decreases were statistically significant in the LAG [BOP, 12.50 (4.87) to 3 (6), p=0.048] and [GI, 0.25 (0.09) to 0.06 (0.12), p=0.048]. Subgingival bacterial count was diminished in the LAG and HAG and was not affected by L. reuteri intake. Conclusions: Chronic alcohol consumption may be considered a risk factor for gingivitis in a dose-dependent manner and L. reuteri supplements could be a useful strategy to treat gingival inflammation caused by chronic alcohol consumption.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the School of Dental Medicine.; Advisor: Driss Zoukhri.; Committee: Paul Stark, Cheen Loo, and Carole Palmer.; Keyword: Dentistry.